Diarrhea Risk Factors of Infant and Children Under Five Years in Indonesia: A Systematic Review of Public Health Academic Studies - Wiku Adisasmito (Makara Journal of Health Research, 2010)
Diarrhea is one of the national public health problems most researched academically in the school of public health. This systematic review research aimed at exploring risk factors of diarrhea involved 18 academic products in the form of graduate thesis and undergraduate final academic paper of School of Public Health University of Indonesia in the year 2000-2005. The subjects (3884, ranging from 65 to 500) of these academic research products were mothers, infants, and children under age of 5. Data were analyzed univariate & bivariate. Most of the literatures used as reference in these research were old diarrhea reference books, publication from Ministry of Health and previous academic research results (i.e. thesis and final academic paper). None of the research instruments reviewed was tested its validity and its realibility. Risk factors most researched were related to environmental factor, i.e. clean water & toilet. The significant mother's risk factors were knowledge, behaviour and hygiene. The significant children's risk factors were nutritional status & brestfeeding. Environmental risk factors associated with access to clean water were source of clean water (average OR=3.19), risk of being contaminated (average OR=7.89), and ownership of the clean water source (average OR=17.25). By t-test, the differences between thesis and undergraduate final academic paper were number of independent variables & literature references used. Overall, the quality of academic research products is not sufficiently qualified.